Quality of Life among Adult Patients with Peptic Ulcer in the City of Sulaimani - Mussa, Yasin; Mohammad, mohammed; Abdulsahib, sanaa (Iraqi National Journal of Nursing Specialties, 2011)
Objectives: To assess the quality of life for adult patients with peptic ulcers in the city of Sulaimani. Methodology: A descriptive study, using the assessment approach was conducted on patients with peptic ulcer disease from January 12th, 2009 to September 30th, 2009. A purposive "non-probability" sample of (100) paƟents (males and females) with peptic ulcers who attended Kurdistan Center for Gastroenterology and Hepatology were selected for the study. A questionnaire was adapted from the World Health Organization quality of life questionnaire (1998) for the purpose of the study. It is comprised of (3) parts that included sociodemographic characteristics form, medical history form and adult peptic ulcers patients’ quality of life (QoL) questionnaire. A pilot study was carried out on (10) paƟents for the period of January 12th through January 28th, 2009 to determine the study quesƟonnaire’s reliability through the use of stability (test-retest method). A panel of (14) experts was involved in the determination of the questionnaire’s content validity. Data were analyzed through the application of the descriptive statistical data analysis approach (frequency, percentage, mean of scores) and inferential statistical data analysis approach (Pearson correlation coefficient and chi-square). Results: The findings of the study indicated that quality of life was affected in physical domain and that age, gender, marital status, and monthly income had significant relationship with quality of life domains. Recommendations: The study recommends that young adults, particularly Individuals with blood group (O) should be highly aware from gastrointestinal (GI) symptoms and avoids risk factors for the development of peptic ulcer disease (PUD). Also, the study recommends providing health assurance and conducting further multi centers studies in order to demonstrate the differences in QoL issues for PUD patients.